2015
DOI: 10.1002/2015gb005086
|View full text |Cite
|
Sign up to set email alerts
|

Increased influence of nitrogen limitation on CO2 emissions from future land use and land use change

Abstract: In the latest projections of future greenhouse gas emissions for the Intergovernmental Panel on Climate Change (IPCC), few Earth System Models included the effect of nitrogen limitation, a key process limiting forest regrowth. Few included forest management (wood harvest). We estimate the impacts of nitrogen limitation on the CO 2 emissions from land use and land use change (LULUC), including wood harvest, for the period 1900-2100. We use a land surface model that includes a fully coupled carbon and nitrogen c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 125 publications
3
26
0
Order By: Relevance
“…A large fraction of biomass nitrogen would be volatilized during clearing and burning of forests. Such nitrogen dynamics with land use change would have significantly reduced available nitrogen for growth, resulting in large decrease in the simulated GPP, especially outside the tropical regions where nitrogen is a limiting nutrient (Jain et al, ; Meiyappan et al, ). The spatial analysis also indicated that the negative effect of land use change on uWUEa was large in several nontropical regions (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…A large fraction of biomass nitrogen would be volatilized during clearing and burning of forests. Such nitrogen dynamics with land use change would have significantly reduced available nitrogen for growth, resulting in large decrease in the simulated GPP, especially outside the tropical regions where nitrogen is a limiting nutrient (Jain et al, ; Meiyappan et al, ). The spatial analysis also indicated that the negative effect of land use change on uWUEa was large in several nontropical regions (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic global vegetation models CABLE-POP Haverd et al 2018Thermal acclimation of photosynthesis; residual stomatal conductance (g0) now non-zero; stomatal conductance set to maximum of g0 and vapour-pressure-deficit-dependent term CLASS-CTEM Melton and Arora (2016) 20 soil layers used. Soil depth is prescribed following Shangguan et al 2017.…”
Section: Bookkeeping Modelsmentioning
confidence: 99%
“…Small adjustments to photosynthesis parameters to compensate for the effect of new climate forcing on GPP. CLASS-CTEMMelton and Arora (2016) 20 soil layers used. Soil depth is prescribed following Pelletier et al(2016).…”
mentioning
confidence: 99%